Mathematical model of stabilization system for data-measuring complex on moving base - Сущенко, О.А. (Proceedings of National Aviation University, 2010)
The paper is devoted to actual problem of measuring-data system stabilization. The trend of the modern measuring-data development is improvement of their accuracy. For measuring-data systems mounted at the moving base the further progress of this tendency is impossible without system stabilization. The paper represents mathematical model of the stabilization system which controls position of data-measuring system mounted at platform in the gimbals with three degrees of freedom. In its turn stabilized platform with stabilized data-measuring system is mounted at the base which carries out angular motion. Using of such platforms provides high accuracy of the stabilization. Mathematical model includes both dynamic and kinematic descriptions of the gimballed platform. In the paper the important obtained results are represented such as expressions for control moments applied to outer gimbal, inner gimbal and platform. Another important result is determination of stabilization speeds and corresponding algorithm of these speeds determination. Efficiency of suggested approach is proved by the represented simulation results. The obtained results may be applied in area of wide class measuring devices stabilization.